The Discrepancy Between Students’ Economic Knowledge and Their Consumption Behavior: A Phenomenological Study at SMAN 1 Kampar Timur, Kampar Timur Subdistrict, Kampar Regency, Riau Province - Yanti Angraini; Daru Wahyuni (International Journal of Applied Research and Innovation, 2026)
This study examines the structural divergence between formal academic comprehension and actualized financial practices among secondary school students. Operating within a nonempirical qualitative phenomenological framework, the research integrates Mezirow Transformative Learning Theory and cognitive dissonance models to map how formal economic concepts fail to transition from cognitive acquisition to affective and konative execution. Utilizing Colaizzi descriptive phenomenological method to analyze lived experiential narratives, the study uncovers an intense intellectual gap where textbook financial literacy is systematically neutralized by external consumer stimuli. The structural findings reveal three dominant behavioral typologies driving adolescent spending choices, which are self gratification, social acceptance, and identity oriented consumption. These patterns are heavily reinforced by persuasive digital choice architectures, algorithmic social media marketing, and immediate peer group survival mechanics that bypass rational utility maximization. The investigation concludes that standard instructional methodologies remain isolated from student lifestyle choices without a pedagogical framework that addresses emotional and social dimensions. To bridge this critical knowledge-behavior gap, educational institutions must restructure current curricula to prioritize reflective critical literacy, character development, and personalized economic self regulation.